Health Care Experiences in Rural, Remote, and Metropolitan Areas of Australia - Sharon L Bourke; Claire Harper; Elianna Johnson; Janet Green; Ligi Anish; Miriam Muduwa; Linda Jones (Rural Nurse Organization; Binghamton University, 2021)
Background: Australia is a vast land with extremes in weather and terrain. Disparities exist between the health of those who reside in the metropolitan areas versus those who reside in the rural and remote areas of the country. Australia has a public health system called Medicare; a basic level of health cover for all Australians that is funded by taxpayers. Most of the hospital and health services are located in metropolitan areas, however for those who live in rural or remote areas the level of health service provision can be lower; with patients required to travel long distances for health care. Purpose: This paper will explore the disparities experienced by Australians who reside in regional and remote areas of Australia. Method: A search of the literature was performed from healthcare databases using the search terms: healthcare, rural and remote Australia, and social determinants of health in Australia. Findings: Life in the rural and remote areas of Australia is identified as challenging compared to the metropolitan areas. Those with chronic illnesses such as diabetes are particularly vulnerable to morbidities associated with poor access to health resources and the lack of service provision. Conclusion: Australia has a world class health system. It has been estimated that 70% of the Australian population resides in large metropolitan areas and remaining 30% distributed across rural and remote communities. This means that 30% of the population are not experiencing their health care as 'world-class', but rather are experiencing huge disparities in their health outcomes. Keywords: rural and remote, health access, mental health issues, social determinants DOI: https://doi.org/10.14574/ojrnhc.v21i1.652